Propuesta de diseño de sistema de control para el sistema térmico de una máquina inyectora de plástico FLLI. Sandretto 6GV/70T. - Brenes-Salinas, Jimmy Yadimir (Instituto Tecnológico de Costa Rica, 2018)
Due to the ine ciency of heating systems in plastic injection machines, and given that the control of melting temperature of plastic is one of the variables that produces the most errors in the nal product, originate the initiative to design a capable system to optimize the systems that are commonly used in this type of machines, which are based on control systems textsl ON / OFF around an input value and thermocouples to measure the temperature. Through this project we present the development of an automatic control system in order to control the melting temperature of plastic in a plastic injection machine, where a mathematical model was created which characterizes the thermal system of a machine of this type, where the resistance of type band, cylinder, plastic and screw without end is taken into account. Subsequently, a simulation of nite elements was performed to observe the behavior of the heat distribution along the cylinder, considering the di erent parts of the structure and the plastic used in the industry. Finally, three di erent controllers (PI, PD, PID) were designed based on the mathematical and empirical model, and were implemented in MatLab's SIMULINK simulation environment, in which vital information could be obtained.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2018.
Keywords: Elementos Finitos; Modelos analíticos; Modelos; Control PIPD- PID; Control; MatLab web server; Research Subject Categories::TECHNOLOGY::Electrical engineering, electronics and photonics::Electronics